2009
DOI: 10.1093/ntr/ntn021
|View full text |Cite
|
Sign up to set email alerts
|

Low-level smoking among Spanish-speaking Latino smokers: Relationships with demographics, tobacco dependence, withdrawal, and cessation

Abstract: reported the least craving in pre-to postcessation longitudinal analyses. Third, despite signifi cant differences on dependence and craving, low-level smoking was not associated with abstinence. Smoking level was not associated with demographic variables.Discussion: This is a preliminary step in understanding factors infl uencing tobacco dependence and smoking cessation among low-level Spanish-speaking Latino smokers, a subgroup with high prevalence in the Latino population. IntroductionAccording to 2005 data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 15 publications
(20 reference statements)
6
48
0
Order By: Relevance
“…In several studies, the WISDM has demonstrated good psychometric properties, such as good internal consistency and concurrent, discriminant, and predictive validity. [10][11][12][13][14][15][16][17] Through an extensive psychometric analysis, Piper et al 15 noted the presence of two synthetic WISDM scales, namely primary dependence motives (PDM) and secondary dependence motives (SDM). PDM is composed of four scales (automaticity, craving, loss of control, and tolerance) and represents the core component of tobacco dependence, whereas SDM is composed of the nine remaining scales.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the WISDM has demonstrated good psychometric properties, such as good internal consistency and concurrent, discriminant, and predictive validity. [10][11][12][13][14][15][16][17] Through an extensive psychometric analysis, Piper et al 15 noted the presence of two synthetic WISDM scales, namely primary dependence motives (PDM) and secondary dependence motives (SDM). PDM is composed of four scales (automaticity, craving, loss of control, and tolerance) and represents the core component of tobacco dependence, whereas SDM is composed of the nine remaining scales.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, light smokers often do not exhibit the same levels of tolerance and withdrawal as do heavier smokers ( Shiffman, Paty, Kassel, Gnys, & Zettler-Segal, 1994 ;Soresi, Catalano, Spatafora, Bonsignore, & Bellia, 2005 ), suggesting that physiological and behavioral factors that are targeted for intervention may need to be modifi ed for this group. Finally, although in a recent trial, low-level smoking was not associated with abstinence at follow-up ( Reitzel et al, 2009 ), one recent study targeting lighter smokers (defi ned as smoking 6 -15 cigarettes/day [cpd]) observed higher abstinence rates for those without a history of heavier smoking at the Week 12 follow-up ( Gariti et al, 2009 ), which suggests that interventions specifi cally targeting low-level smokers may increase effi cacy.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Numerous studies have documented higher rates of nondaily (ie, smoking on only some days) or light smoking (ie, 10 or fewer cigarettes per day [CPD]) among Latinos compared with non-Latino Whites. 15,[18][19][20][21][22] Nondaily smoking is under-studied and undertreated, 22,23 despite its association with significant health risks, [24][25][26][27] making it an important target for study. Additionally, a nuanced analysis demonstrates that significant proportions of Latino smokliefs, and behaviors of one's heritage culture with those of a new culture.…”
Section: Smoking and Acculturation Among Latinos -Pulvers Et Almentioning
confidence: 99%